2012
DOI: 10.1002/jhm.1983
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of curbside versus formal consultations

Abstract: Palladium‐catalyzed Mizoroki–Heck reactions were carried out in the presence of calcium carbonate in alcoholic solvents. Under these conditions an efficient preparation of functionalized benzalacetones was developed. The reactions were carried out at room temperature and aerobic conditions, giving the products within several minutes in up to 95% isolated yields. Furthermore, some kinetic investigations, mechanistic insights and considerations are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…On multivariate analysis, lack of infectious diseases consultation within 1 week [OR 3.56 (1.59-7.94), P ¼ 0.002] or telephone consultation [OR 2.31 (1.22-4.38), P ¼ 0.01] was associated with increased 90-day mortality, compared with those patients for whom infectious diseases performed a bedside consultation [32 && ]. In a recent study from the general hospitalist literature in which telephone, or curbside, consultations were followed up by formal bedside consultations, authors found that information provided by requesting providers was inaccurate or incomplete in 51% of curbside consultations [33]. This resulted in a change of management advice for 60% of patients compared with curbside consultation [33].…”
Section: Bedside or Curbside?mentioning
confidence: 94%
See 2 more Smart Citations
“…On multivariate analysis, lack of infectious diseases consultation within 1 week [OR 3.56 (1.59-7.94), P ¼ 0.002] or telephone consultation [OR 2.31 (1.22-4.38), P ¼ 0.01] was associated with increased 90-day mortality, compared with those patients for whom infectious diseases performed a bedside consultation [32 && ]. In a recent study from the general hospitalist literature in which telephone, or curbside, consultations were followed up by formal bedside consultations, authors found that information provided by requesting providers was inaccurate or incomplete in 51% of curbside consultations [33]. This resulted in a change of management advice for 60% of patients compared with curbside consultation [33].…”
Section: Bedside or Curbside?mentioning
confidence: 94%
“…In a recent study from the general hospitalist literature in which telephone, or curbside, consultations were followed up by formal bedside consultations, authors found that information provided by requesting providers was inaccurate or incomplete in 51% of curbside consultations [33]. This resulted in a change of management advice for 60% of patients compared with curbside consultation [33]. In summary, telephone or curbside consultation, although comprising as many as 17% of consults [30], appears inferior to bedside consultation, providing inaccurate information [33] that may result in increased mortality [32 && ].…”
Section: Bedside or Curbside?mentioning
confidence: 97%
See 1 more Smart Citation
“…The potential dangers of curbside consultations illustrated in the study by Burden et al 6 should not be trivialized. However, we disagree with the premise that face-to-face consultation is always the criterion standard against which curbside consultation should be compared.…”
Section: In Replydcurbside Consultations: a Call For More Investigatimentioning
confidence: 95%
“…Benefits and costs have each been represented in both monetary outcomes (reduced fee-for-service payments and overhead and downstream costs 2 vs lost revenue 3 ) and nonmonetary outcomes (eg, measurable practice efficiencies 4 and intangible favorable impact on institutional culture 1,5 vs risks to patient safety 6 ). The potential dangers of curbside consultations illustrated in the study by Burden et al 6 should not be trivialized. However, we disagree with the premise that face-to-face consultation is always the criterion standard against which curbside consultation should be compared.…”
Section: In Replydcurbside Consultations: a Call For More Investigatimentioning
confidence: 97%